Instructions to the Jury: Summary Without Comment - Curtis Wright Jr. (Washington University Law Quarterly, 1954)
Any attempt at sensible explanation requires state-by-state discussion. For the time being, therefore, it is simply mentioned that the merits or demerits of the "mere colorless summary" are hardly a profitable subject of discussion if it be true, as this paper contends, that in truth the instruction process of an overwhelming majority of the states stops very considerably short thereof.
Keywords: Instructions to juries